Reducing the Incidence of Substance Use Disorders in Anesthesiology Residents: 13 Years of Comprehensive Urine Drug Screening. (October 2018) - Fitzsimons, Michael G.; Baker, Keith; Malhotra, Rajeev; Gottlieb, Andrew; Lowenstein, Edward; Zapol, Warren M.
Editor's Perspective: What We Already Know about This Topic: Substance abuse remains common among anesthesia clinicians Whether routine, random drug testing deters use remains unknown What This Article Tells Us That Is New: The Massachusetts General Hospital randomly tested residents over a period of 13 yr There was no detected substance abuse among residents during the testing period in 1, 002 resident years, versus four incidents in the previous 719 resident years This intriguing, but statistically fragile, result needs to be confirmed in other settings and other anesthesia clinicians Background: The incidence of substance use disorders in the United States among residents in anesthesiology is between 1% and 2%. A recent study reported that the incidence of substance use disorders in U.S. anesthesiology residents has been increasing. There are no reports of effective methods to prevent substance use disorder in residents. A comprehensive drug testing program including a random component may reduce the incidence of substance use disorders. Methods: The authors initiated a comprehensive urine drug screening program of residents, fellows, faculty physicians, and certified nurse anesthetists. The authors performed 3, 190 tests over 13 yr. The authors determined the incidence of substance use disorders among residents in our large anesthesiology residency program during the decade before (January 1, 1994, to December 31, 2003) and for the 13 yr after (January 1, 2004 to December 31, 2016) instituting a random urine drug testing program. A total of 628 residents trained in the program over these 23 yr; they contributed a total of 1, 721 resident years for analysis. Fewer faculty and certified nurse anesthetists were studied, so we do not include them in our analysis. Results: The incidence of substance use disorders among trainees in our department during the 10 yr before initiation of urine drug screening was four incidents in 719 resident years or 0.0056 incidents per resident-year. In the 13 yr after the introduction of urine drug screening, there have been zero incidents in 1, 002 resident years in our residency program ( P = 0.0305). Conclusions: This single-center, comprehensive program including preplacement and random drug testing was associated with a reduction of the incidence of substance use disorders among our residents in anesthesiology. There were no instances of substance use disorders in our residents over the recent 13 yr. A large, multicenter trial of a more diverse sample of academic, government, and community institutions is needed to determine if such a program can predictably reduce the incidence of substance use disorders in a larger group of anesthesiology residents. Abstract : The Massachusetts General Hospital randomly tested residents over a period of 13 yr. There was no detected substance abuse among residents during the testing period in 1, 002 resident years, versus four incidents in the previous 719 resident years. This intriguing, but statistically fragile, result needs to be confirmed in other settings and other anesthesia clinicians.